2013
DOI: 10.1007/s00264-013-1994-2
|View full text |Cite
|
Sign up to set email alerts
|

Nodular giant cell tumour of the tendon sheath of the hand: analysis of eighty-four cases—diagnostic decisions and outcome

Abstract: Our data on the nodular GCTTS are in accordance with published data concerning the age distribution, gender distribution, and localisation. No soft-tissue imaging method is superior for the diagnosis of nodular GCTTS or for the preoperative planning. A preoperative MRI may not be necessary as clinical and ultrasound examination are sufficient. To exclude bony erosions, a preoperative X-ray is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 15 publications
(24 reference statements)
1
25
0
15
Order By: Relevance
“…Reported recurrence rates of GCTTSs differ in the literature. During 31.5 months of follow-up, a 2.4% recurrence rate was noted in a study of 84 patients by Lautenbach et al (18) Darwish and Haddad reported a recurrence rate of 24% after excision of GCTTSs in a study of 52 patients; the GCTTSs most commonly arose from the thumb. (19) In contrast, most of the GCTTSs in our study occurred on the index finger, with none arising from the thumb.…”
Section: Discussionmentioning
confidence: 95%
“…Reported recurrence rates of GCTTSs differ in the literature. During 31.5 months of follow-up, a 2.4% recurrence rate was noted in a study of 84 patients by Lautenbach et al (18) Darwish and Haddad reported a recurrence rate of 24% after excision of GCTTSs in a study of 52 patients; the GCTTSs most commonly arose from the thumb. (19) In contrast, most of the GCTTSs in our study occurred on the index finger, with none arising from the thumb.…”
Section: Discussionmentioning
confidence: 95%
“…4,5 It can be seen at any age but mostly affects individuals in their third to fifth decades of life and is mostly seen in females. [6][7][8] GCTTS has not previously been reported in a pregnant woman. Etiology of GCTTS is not clear but there are many risk factors mentioned in the literature such as trauma, infection, vascular abnormality, lipid metabolism disorders, osteoclastic proliferation, and immune system disorders.…”
mentioning
confidence: 74%
“…Although the GCTTS, also known as the pigmentedvillonodular tumor of the tendon sheath, is a benign nodular tumor of the hand arising from the tendon sheaths, 5,8 the incidence of cases originating from the foot and ankle is increasing. 1,2 The localized GCTTS especially affects the small joints in the limb and usually presents as a solid-solitary soft-tissue mass, but simultaneous multi-fragmented lesions in the foot are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico diferencial clínico es extenso. La ecografía identificaría una lesión sólida, generalmente homogénea, hipo o hiperecoica o, en menos ocasiones, heterogénea, con vascularización aumentada en el estudio Doppler, y en relación con la vaina del tendón, con el que no se moviliza por ese motivo [6][7][8] . También permitiría descubrir lesiones satélites y, aunque podría confundirse con quistes sinoviales rotos, la confusión no tiene trascendencia terapéutica si se interviene.…”
Section: Comentario/discusiónunclassified
“…Entre las pruebas complementarias de imagen, la RM es considerada por algunos como la prueba de imagen más precisa para el diagnóstico 4,7,8 , El tratamiento de los TCGVT se basa en la extirpación completa de la lesión. La técnica parece más fiable con exposiciones amplias y usando gafas de aumento o instrumental microquirúrgico 6,9 . La radioterapia, aunque controvertida, podría indicarse en los casos con más riesgo de recidiva (con mitosis, compromiso óseo o resección lesional incompleta).…”
Section: Comentario/discusiónunclassified